Dynamics of diuron and sulfentrazone formulations in soils with different textures - Matos, Ana K. A. [UNESP] (2020)
Background: The use of commercial mix and tank mix with two or more herbicides is a widespread practice. However, despite its several possible benefits, little is known about its effect on the behavior of the molecules in the soil, which can increase or reduce the leaching potential of these molecules. Objective: This study evaluated the leaching potential of the herbicides diuron and sulfentrazone applied, using commercial mix and tank mix, in soils with different textures. Methods: The herbicides diuron (1,750 g ha-1) and sulfentrazone (875 g ha-1) were applied in three soils with different textures (clayey, medium, and sandy), using a commercial mix (Stone® ) and a tank mix (Herburon 500 BR + Boral® ). Subsequently, the treated soils were reconstituted in soil columns subjected to rainfall simulations with accumulated rainfall volumes of 40, 80, and 120 mm; the leached solutions were collected and analyzed by LC-MS/MS. Results: The results indicated a low descending movement of diuron in the three soils evaluated, when applied using commercial and tank mixes with sulfentrazone. Higher rainfall volumes (80 and 120 mm) were required to increase the diuron movement (≈20% of diuron applied). Sulfentrazone showed a high leaching potential in the soils, whereas the tank mix increased the leaching potential in sandy soil with the rainfall depths of 80 and 120 mm. Conclusions: The formulations did not affect the leaching potential of the herbicides in clayey and medium soil. However, the tank mix promoted greater leaching of the herbicides in the sandy soil when compared to the commercial mix.